2020
DOI: 10.3390/su12062308
|View full text |Cite
|
Sign up to set email alerts
|

Credible Sources of Information Regarding Induced Seismicity

Abstract: The central United States has seen an increase in earthquakes in recent years, spurring academics to research this new hazard and communicate their findings to the public-that the earthquakes are human-induced and tied to activities associated with oil and gas development. However, individuals receive information from a variety of sources and accept or reject information based on how credible they view the information source. Within this study, we administered and analyzed a household survey to understand what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Observed patterns can be explained by various factors influencing students' behavior in seeking information about disasters [173]. Students achieving outstanding academic results may prioritize reliable and credible sources of information [174]. Their academic success may also reflect their ability to critically evaluate information and effectively use it in their studies [175].…”
Section: Discussion Related To Students' Insights On School-based Dis...mentioning
confidence: 99%
“…Observed patterns can be explained by various factors influencing students' behavior in seeking information about disasters [173]. Students achieving outstanding academic results may prioritize reliable and credible sources of information [174]. Their academic success may also reflect their ability to critically evaluate information and effectively use it in their studies [175].…”
Section: Discussion Related To Students' Insights On School-based Dis...mentioning
confidence: 99%
“…Observed patterns can be explained by various factors influencing students' behavior in seeking information about disasters [166]. Students achieving outstanding academic results may prioritize reliable and credible sources of information [167]. Their academic success may also reflect their ability to critically evaluate information and effectively use it in their studies [168].…”
Section: Discussion Related To Students' Insights On School-based Dis...mentioning
confidence: 99%
“…Wei and Lindell (2017) also used the mean value of the adoption of each response and provide an overall emergency preparedness (danger control response) score for a specific hazard. While focusing on individual risk responses provides detailed information on each adjustment activity, the mixed results in the literature (e.g., Botzenet al, 2019;Reynaud et al, 2013;Tracy & Javernick-Will, 2020;Wu et al, 2020) and lack of interpretability (Perry & Lindell, 1990) reduce the practical value of these findings for emergency management professionals. For example, while Reynaud et al (2013) reported that flood risk perception leads to the adoption of home elevation, Botzen et al (2019) did not find a significant impact of flood risk perception on home elevation.…”
Section: Eppm In Hazards Researchmentioning
confidence: 99%
“…As with tornado adjustment studies, many of these studies explore why people consider adopting general and hazard‐specific individual danger control responses (often referred to as protective hazard adjustments), such as developing a household emergency plan, storing food and water, or installing earthquake latches. In many cases, the drivers of adjustments, and importance of individual drivers, varies across adjustments and across hazards (Tracy & Javernick‐Will, 2020; Wu et al., 2020). In addition, while some of these studies have considered multiple hazards, none that we reviewed have explored how these factors affect the level, or number of hazard adjustments households adopted.…”
Section: Introductionmentioning
confidence: 99%